Loss of microbial diversity weakens specific soil functions, but increases soil ecosystem stability. (February 2023) - Yang, Xueling; Cheng, Jie; Franks, Ashley E.; Huang, Xiaowei; Yang, Qi; Cheng, Zhongyi; Liu, Yuanhui; Ma, Bin; Xu, Jianming; He, Yan
Abstract: The importance of microbial community diversity for soil functioning is still debated. Here, we used a dilution approach (undiluted, and 10 −4, 10 −8 and 10 −12 ) and supplementation of N nutrient and electron donors to reveal the response of specialized soil functions (lindane removal, methanogenesis and Fe(III) reduction) and microbiome stability in an eutrophic environment. Contrasting to our previous findings in oligotrophic condition, the loss of diversity delayed lindane degradation (with residual concentration of 11.88 mg kg −1 on an average in diluted vs 1.23 mg kg −1 in undiluted), as well as significantly inhibited Fe(III) reduction and methanogenesis. Dilution under eutrophic conditions also weakened the coupling intensity between lindane degradation and methanogenesis, associating with the abundance reduction of specialized dechlorinators and methanogens. However, decline of microbial diversity significantly aggravated the microbial respiration. Microbial co-occurrence networks under diversity loss became more robust, with microbiome stability significantly correlated with abundant species and network complexity. Collectively, nutrient status determined the interaction strength among functional bacterial and archaeal groups, thereby driving contrast in the dependence of specialized and generalist soil functioning on microbial diversity. These findings provide new insights into improved evaluation of carbon loss and extended diversity-functioning relationships to a multi-factor context. Highlights: Microbial diversity loss limits the specialized soil functioning. Dilution led to the increase of soil respiration. Microbiome with lower diversity under eutrophic condition tended to be more stable. Nutrient status changed the dependence of soil functioning on microbial diversity.